Intelligent Controller Design For Multifunctional Prosthetics Hand - Ghazali, Rozaimi; Saad, Mohammad Zyzerull; Syed Hussien, Sharifah Yuslinda; Jali, Mohd Hafiz; Zohedi, Fauzal Naim; Ahmad Izzuddin, Tarmizi (International Journal Of Mechanical Engineering And Robotics Research (IJMERR), 2017)
Prosthetics hand is replacement of original hands that lose or damage because of war, trauma, accident or congenital anomalies. However, problems often occur on a prosthetics hand when dealing with the control capabilities and devising functional. Thus, an advanced mechanical design with control approach is required to improve the performance in terms of quality control in prosthetics hand and also enhance existing capabilities to the optimum level. This paper aims to develop a functional prosthetics hand at upper limb, which will focus on position of human hand particularly using the movement of finger instructions. In this paper, an intelligent controller, Fuzzy with Proportional-Integral-Derivative (Fuzzy-PID) controller is proposed to realize accurate force control with high performance. The performance of prosthetics hand model controlled by Fuzzy-PID controller is outperform the conventional PID controller and Fuzzy controller, where the improvement of the transient response and steady state error is achieved. Performance comparison of three different controllers has been presented through these evaluation process.